Rectal cancer: Watch-and-wait and continuing the rectal-preserving strategy with local excision for incomplete response or limited regrowth. (June 2021) - Al-Najami, Issam; Jones, Helen JS.; Dickson, Edward A.; Muirhead, Rebecca; Deding, Ulrik; James, David RC.; Cunningham, Chris
Abstract: Background: Deferral of conventional surgery for rectal cancer after neo-adjuvant chemo-radiotherapy is gaining increasing interest, particularly for patients who are too frail to undergo major surgery but also those who wish to avoid the adverse effects of major surgery. We elected to undertake a pragmatic approach to include all comers in a cohort with the aim of reflecting the clinical outcomes for patients on a deferral from conventional rectal surgery pathway, treated with neo-adjuvant chemo-radiation (CRT) with or without selective local excision (LE) offered to those who failed to demonstrate a complete clinical response (cCR). Methods: Rectal cancer patients treated with neo-adjuvant CRT were stratified to a group of complete responders to CRT on a "watch and wait" (WW) pathway and a group who were treated with an additional local excision for persistent tumour. Results: Regrowth was noted in 26% (11/42) in the WW group after 2 years surveillance, disease free survival was 94.5% (80–99%) at 1 year and 74.9% (44–76.4%) at 3 years. Recurrence was noted in 45% (10/22) in the CRT + LE group, disease free survival at 1 and 3 years was 74% (53.4–88.1) and 66.2% (45.6–82.4) respectively. Conclusion: A WW strategy for cCR is a viable pathway in the non-operative management of rectal cancer. We found the use of CRT + LE is a useful option for those who hope to avoid surgery but caution should be exercised due to substantially higher risk of recurrence. Highlights: CRT with or without TEM for rectal cancer is a viable way for deferral from surgery.